Peranan Motivasi dalam Meningkatkan Kinerja Pegawai Berbasis Kebutuhan - Anastacia, Dyta; Nasution, Irwan; Suharyanto, Agung (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
This study aims to determine the role of motivation and its inhibiting factors in improving the performance of employees based on needs at the Class IV Port Authority and Port Authority Office Tanjungbalai Asahan. The problem is focused on motivation based on the level of need. In order to approach this problem, Abraham Maslow's theoretical reference is used. The data were collected through literature, observation, interviews, and documentation and analyzed qualitatively. This study concludes that motivation based on the level of need according to Maslow has been well applied to the Class IV Tanjungbalai Asahan Harbormaster and Port Authority offices, namely 1) physical needs in the form of providing office facilities have been fulfilled. 2) Security Needs, from safety appeals in the use of masks and the application of civil servant discipline laws as motivation at work. 3) Social needs from the strength of kinship ties, through directives and mutual coordination and cooperation between agencies. 4) need for appreciation, namely giving responsibility and retirement certificates or giving souvenirs from leaders as motivation. 5) Self-actualization of training development by attending training according to the needs of each diploma and field of work. The motivational barrier given is the funding factor in taking education such as education and training because it takes a long time and the education costs are borne by themselves.